The Level of Knowledge, Attitudes and Behavior Regarding Cataracts of The Elderly Around The Primary Care Center Semarang - Jacob, Ni Made Helen Virginia; Nugroho, Trilaksana; Dharma, Andhika Guna (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Introduction: Cataract is the major cause of reversible blindness and visual impairment in developing countries. It has been assumed that there is poor access to information related to the cause, prevention, and treatment of cataracts in developing countries. There is also a paucity of data on knowledge, attitude, and behavior toward cataracts in Semarang. Objective: To determine the Knowledge, Attitudes, and Behavior Regarding Cataracts of The Elderly around the Primary Care Center Semarang Method: A community-based cross-sectional study was conducted among 40 participants in November 2019. The study participants were selected by a simple random sampling method. Data were collected with a structured questionnaire by using face-to-face interviews. The data were entered into Microsoft Excel 2016 and analyzed using Statistical Package for Social Sciences (SPSS) version 25. The level of statistical significance was set at a p-value less than 0.05. The Socio-demographic factor as Gender, Age, Education, Occupation, and Income set as independent variable in this study. Result: There were 40 respondents, based on questionnaire data 52,50% of respondents had good knowledge, 85% had a good attitude, and 60% had poor behavior. The Education and Knowledge (p=0,001), Education and Behavior (p=0,004), Knowledge and Behavior (0.57749p>0,5, Gender, Education and Income (p>0,05), Education and Income (p>0,05)had positive significant on the variables. Conclusion: A Good approach strategy is needed to achieve to increase public Knowledge, Attitude, and Behavior like doing health promotion periodically and improving health care performance, and facilitate their availability in primary care.